progress of sciences and knowledges (Iraqi Journal of Civil Engineering, 2008)
With the progress of sciences and knowledges, the development in the fieldof earth observation and measurements necessary ones, which helped inovercoming the problem of the time and cost required by field surveys in thedivision of agricultural land. In this study were recruited technical remotesensing, geographic information systems and field surveys for the purpose ofassessing the accuracy of the division of agricultural land for agricultural arealocated in the eastern part of the Ramadi city as they were deducted fromGoogle Earth. Comparison with the other conventional methods, the use ofremote sensing and GIS gives adequate accuracy in the area of the division ofagricultural land